2009
DOI: 10.1002/adsc.200800672
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Supported Ionic Liquid Phase (SILP) Catalyst for Slurry‐Phase Friedel–Crafts Alkylations of Cumene

Abstract: A supported ionic liquid phase (SILP) catalyst material has been developed based on a silica support coated with an acidic chloroaluminate ionic liquid. Compared to the results in a liquid-liquid biphasic reaction these materials showed in the isopropylation of cumene a clearly different selectivity which was found to be related to a reduction of the ionic liquids acidity by the untreated silica support. By pretreating the support with a defined amount of ionic liquid for neutralization and removal of surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(27 citation statements)
references
References 37 publications
0
26
1
Order By: Relevance
“…Initially [140,141]. The time required to reach 80% conversion was six times shorter with SILP, compared to the liquid-liquid biphasic reaction using the same ionic liquid.…”
Section: Silp and Scillmentioning
confidence: 97%
“…Initially [140,141]. The time required to reach 80% conversion was six times shorter with SILP, compared to the liquid-liquid biphasic reaction using the same ionic liquid.…”
Section: Silp and Scillmentioning
confidence: 97%
“…Joni et al developed a well-defined and optimized pretreatment of silica support materials prior to impregnation with an acidic chloroaluminate IL [88]. A solution of n([C 2 C 1 Im]Cl)/n(AlCl 3 ) = 1/2 and DCM was contacted with the calcined silica.…”
Section: Supported Ionic Liquid Phase (Silp) Catalysismentioning
confidence: 99%
“…These SILP catalysts were successfully tested in the slurry-phase Friedel-Crafts alkylation of cumene and in the continuous gas-phase isopropylation of cumene and toluene. The catalysts operated with constant high selectivity and unchanged catalytic activity for 210 h time-on-stream [88,89].…”
Section: Supported Ionic Liquid Phase (Silp) Catalysismentioning
confidence: 99%
“…observed that the performance of the Rh‐catalysed hydroformylation using propene was strongly linked to ionic liquid loading on the silica support 8a. In addition, following optimisation of the acidic chloroaluminate SILP catalyst for a slurry phase Friedel–Crafts alkylation of cumene, a critical ionic liquid loading value was found to be necessary to overcome the neutralisation of the chloroaluminate with the surface silanol groups on the silica 19…”
Section: Resultsmentioning
confidence: 99%